2010
DOI: 10.1111/j.1939-165x.2010.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL RESEARCH: Comparison of methods for depletion of albumin and IgG from equine serum

Abstract: Albumin and IgG removal kits optimized for human use have variable efficacy for equine serum. Combined use of the ProteoExtract kit and manual incubation with protein G Sepharose beads provided the most effective depletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Using crude plasma for 2-DE leads to overloading of abundant proteins and poor spot resolution. Thus, albumin removal is a crucial preparation step for plasma proteome investigation with in-gel methods (Olver et al 2010). In present work we tested four different albumin removal strategies for in-gel proteomic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Using crude plasma for 2-DE leads to overloading of abundant proteins and poor spot resolution. Thus, albumin removal is a crucial preparation step for plasma proteome investigation with in-gel methods (Olver et al 2010). In present work we tested four different albumin removal strategies for in-gel proteomic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the results of Chen et al [ 3 ], who reported that 5–10% TCA in acetone is the optimal condition for removing human albumin and IgG, but Liu et al [ 14 ] reported that 1% TCA in isopropanol is the optimal solution to remove albumin from human and monkey serum for a proteomic study. Notably, our protocol is simple and inexpensive, and it is more efficient than using human commercial kits to remove equine serum albumin and IgG [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In human analyses, serum/plasma albumin is usually depleted by using column immunoaffinity purification or commercial albumin removal kits [ 30 ]. Unfortunately, there is no commercial kit available specifically for horses, and most kits for human samples inefficiently remove equine albumin [ 22 ]. Additionally, there is also a lack of published reports relating to the protocol of serum albumin removal in horses.…”
mentioning
confidence: 99%
“…Serum albumin is synthesized mainly in the liver (1) and secreted into blood where it constitutes almost 50% of the proteins in the serum (25). Albumin also produces the majority of the protein contents of extracellular fluids such as interstitial, cerebrospinal, and lymphatic (2,6,7).…”
Section: Introductionmentioning
confidence: 99%